Urban housing prices and consumption structure upgrading: different relationships in urban and rural China - Ding, Yemin; Chin, Lee; Taghizadeh-Hesary, Farhad (Vilnius Gediminas Technical University, 2024)
The dynamics of housing prices can play a pivotal role in shaping household behavior. Motivated by the limited research on the impact of housing prices on consumption structure upgrading in China, this paper presents a series of analyses that deploy panel data from 276 Chinese cities between 2005 and 2019 to scrutinize this impact. Firstly, a fixed effect model was used to investigate the relationship between urban housing price and the consumption structure upgrading, and it was found that urban housing price has an inverted U-shaped effect on the consumption structure upgrading of Chinese urban residents, while it has an inhibitory effect on the consumption structure upgrading of Chinese rural residents. Then, we conducted multiple robustness tests, all of which corroborated the benchmark results’ reliability. Finally, deeper than existing research, the mechanism of the impact of urban housing prices on the consumption structure upgrading was further explored and it was found that increasing urban housing prices can affect consumption structure upgrading by affecting residents’ marginal propensity to consume in development and enjoyment. Our findings provide key alternatives for China’s government to promote residents’ consumption structure upgrading.